Explorando o potencial do CO2 por meio dos líquidos iônicos de fase suportados para produção de carbonatos cíclicos - Silva, Blendo Almeida da (2024)
The fixation of CO2 into cyclic carbonates is a highly efficient synthetic route, recognized for its atomic economy and wide utility. Ionic Liquids have garnered interest due to their CO2 absorption capacity and chemical stability, making them attractive study targets. This work proposes investigating SILP catalysts for converting epoxides into cyclic carbonates under mild reaction conditions. The catalysts of trichlorozincate of 1-methyl-3-(3- (trimethoxysilyl)propyl)imidazolium, chloride of 1-methyl-3- (trimethoxysilylpropyl)pyridinium, and chloride of 1-methyl-3-(3- (trimethoxysilyl)propyl)imidazolium were synthesized, supported on Al2O3, and characterized by nuclear magnetic resonance, infrared absorption spectroscopy, and thermal analysis. The catalytic study of the SILP-Cl catalyst, it was observed that epoxides containing electron-withdrawing groups in their structure showed the best results, with epichlorohydrin achieving 100% conversion. Additionally, 2-(phenoxymethyl)oxirane (entry 2) and 2-((o-tolyl oxy)methyl)oxirane showed conversion results close to 90%, along with small epoxides like propylene oxide and 1,2-epoxybutane, which also showed satisfactory results. For the SILP-ZnCl3- catalyst, the results were similar to those obtained by the SILP-Cl catalyst, especially under the condition of 100 mg of catalyst and 120°C. Epoxides without this electron-withdrawing effect achieved low conversion values, such as tert-butyl glycidyl ether, which reached around 30% conversion. However, both catalysts maintained high selectivity for cyclic carbonate production. The recyclability tests of the catalyst demonstrated slightly decreased in conversion over four cycles, while maintaining selectivity above 90% without catalyst leaching. The obtained results indicate the efficacy of the established reaction conditions, highlighting the influence of the size and structure of the epoxides on conversion and selectivity.